Analysis of Internal Control over Finished Goods Inventory in Improving Operational Effectiveness at PT Winner Prima Selaras - Ridwan Syahid; Mardani Supranata (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study aims to evaluate the effectiveness of internal control over finished goods inventory implemented at PT Winner Prima Selaras. The research seeks to determine whether the existing internal control system has been adequately designed and applied to support effective inventory management. A quantitative analysis method was employed in this study to provide an objective assessment based on measurable data. Data collection was conducted using documentation and field notes obtained directly from PT Winner Prima Selaras. The data sources included both primary data and supporting documents, gathered through question-and-answer sessions with relevant personnel as well as documentation available at the research site. These data provided insight into the company’s inventory management practices and internal control procedures. The data analysis technique involved examining and comparing theories related to inventory turnover and control effectiveness with the actual practices implemented by the company. Inventory turnover ratios were analyzed to assess whether the movement of finished goods aligned with the standards established by the company. The results of the study indicate that the internal control of finished goods inventory at PT Winner Prima Selaras has not yet been fully effective. This conclusion is evidenced by inconsistencies in the monthly execution of finished goods inventory turnover when compared to the company’s predetermined standards during the 2016 period. Consequently, improvements in inventory control procedures are necessary to enhance operational effectiveness and ensure better inventory management performance.